PFAS contamination in Texas Gulf Coast estuarine sediments and impacts of environmentally informed concentrations on early life stage sheepshead minnow (Cyprinodon variegatus) - Kerri Lynn Ackerly; Grace Walsh; Kathleen Roark; Elizabeth DiBona; Raegan Osentowski; Tamara Rivera; Lu Lin; Kristin M. Nielsen (Environmental Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Rapid Onset and Short Duration of TrenibotulinumtoxinE for Treatment of Moderate to Severe Glabellar Lines: Efficacy and Safety Results from a Phase 3 Study - Marion Moers-Carpi; Cheryl Burgess; Brian Biesman; Deirdre Hooper; Alexander Rivkin; Chung-Yi Chiang; Grace S. Park; Amy Weitzenfeld; Joan-En Chang-Lin (Toxicon, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Beyond the check-up: how well-child exams, pediatric specialists, and provider recommendations can close HPV vaccine gaps for Chinese American Teens - Lin Zhu; Xinrui Li; Elaine Zhiqing Liu; Philip T. Siu; Shumenghui Zhai; Chun Pan; Nikki Cao; Grace X. Ma (Cancer Causes & Control, 2026)
Purpose This study aimed to identify provider- and practice-level factors influencing human papillomavirus (HPV) vaccine uptake among Chinese American (CA) adolescents. Despite increasing public health efforts, HPV vaccination rates in this population remain suboptimal, and knowledge on the link between provider/practice characteristics and vaccine uptake is limited. Methods We analyzed data from 1,272 CA adolescents (aged 13–17) using the National Immunization Survey-Teen (2015–2019) datasets. Key measures included HPV vaccine initiation and completion (based on proxy reporting and verification), accompanied by various multilevel factors: provider-level (recommendation, specialty), practice-level (facility type, vaccine acquisition, well-child exam), parent-level (mother’s education, marital status), and adolescent-level characteristics. Weighted descriptive statistics and stepwise multivariate logistic regression were used to examine associations. Results Overall, 71.22% of CA adolescents initiated at least one HPV vaccine dose, while 48.14% completed the regimen. Provider's recommendation (initiation OR = 21.50, completion OR = 8.12), having a pediatrician (initiation OR = 5.37, completion OR = 3.20), and receiving the 11–12-year-old well-child exams significantly predict both initiation and completion. Regional disparities were observed, with adolescents in the Northeast and West showing higher completion rates than those in the South. Unexpectedly, adolescents not enrolled in school and those with mothers who had less than 12 years of education or were unmarried showed higher completion rates. Conclusion Provider recommendations and pediatric care are crucial for improving HPV vaccination rates among CA adolescents. Addressing regional disparities and implementing targeted interventions, including enhanced provider training focused on culturally sensitive communication, are essential to dismantle systemic barriers and improve comprehensive vaccination coverage in this underserved population.

Plasticity and regional heterothermy of upper thermal tolerance in the ring-necked snake - Christian L. Cox; Kelly Lin Wuthrich; Dareen Aloudeh; Samuel J. Baker; Anna G. Climo; Alexa F. Gross; Christian W. Kizer; Zoe M. Korff; Oscar Melendez Vera; Veronica Y. Silva; Alexis M. Spans; Grace R. Thilenius; et al. (Journal of Thermal Biology, 2026)

Analytical framework for fast identification of hydrogeological boundaries and aquifer parameters in confined aquifers - Fu-Kuo Huang; Ying-Fan Lin; Hund-Der Yeh; Grace S. Wang (Journal of Hydrology, 2025)

Tidal signal propagation in coastal aquifers considering semi-permeable boundaries and partial penetration effects - Fu-Kuo Huang; Ying-Fan Lin; Grace S. Wang; Barret L. Kurylyk (Journal of Hydrology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Colloidal and interfacial properties of spray dried pulse protein-blueberry polyphenol particles in model dispersion systems - Yufeng Lin; Nicholas Cheng; Yueyue Jiang; Mary H. Grace; Mary Ann Lila; Roberta Targino Hoskin; Haotian Zheng (Food Chemistry, 2024)

Development of 3D-iNET ORION: a novel, pre-clinical, three-dimensional in vitro cell model for modeling human metastatic neuroendocrine tumor of the pancreas - Jan Strnadel; Mark A. Valasek; Grace Y. Lin; Huahui Lin; Ann M. Ponsford Tipps; Sang Myung Woo; Ken Fujimura; Huawei Wang; Sunkyu Choi; Jack Bui; Christopher Hermosillo; Kristen Jepsen; et al. (Human Cell, 2024)
Neuroendocrine tumors (NETs) of the pancreas are rare neoplasms that present complex challenges to diagnosis and treatment due to their indolent course. The incidence of pancreatic neuroendocrine tumors has increased significantly over the past two decades. A limited number of pancreatic neuroendocrine cell lines are currently available for the research. Here, we present 3D-iNET ORION, a novel 3-dimensional (spheroid) cell line, isolated from human pancreatic neuroendocrine tumor liver metastasis. Three-dimensionally grown (3D) cancer cell lines have gained interest over the past years as 3D cancer cell lines better recapitulate the in vivo structure of tumors, and are more suitable for in vitro and in vivo experiments. 3D-iNET ORION cancer cell line showed high potential to form tumorspheres when embedded in Matrigel matrix and expresses synaptophysin and EpCAM. Electron microscopy analysis of cancer cell line proved the presence of dense neurosecretory granules. When xenografted into athymic mice, 3D-iNET ORION cells produce slow-growing tumors, positive for chromogranin and synaptophysin. Human Core Exome Panel Analysis has shown that 3DiNET ORION cell line retains the genetic aberration profile detected in the original tumor. In conclusion, our newly developed neuroendocrine cancer cell line can be considered as a new research tool for in vitro and in vivo experiments.

Meeting the heavy-metal safety requirements for food crops by using biochar: An investigation using sunflower as a representative plant under different atmospheric CO2 concentrations - Yiying Wang; Guiying Lin; Xian Li; Ming Hang Tai; Shuang Song; Hugh Tiang Wah Tan; Ken Leong; Elvis Yew Boon Yip; Grace Yoke Chin Lee; Yanjun Dai; Chi-Hwa Wang (Science of The Total Environment, 2023)

How can diverse national food and land-use priorities be reconciled with global sustainability targets? Lessons from the FABLE initiative - Aline Mosnier; Guido Schmidt-Traub; Michael Obersteiner; Sarah Jones; Valeria Javalera-Rincon; Fabrice DeClerck; Marcus Thomson; Frank Sperling; Paula Harrison; Katya Pérez-Guzmán; Gordon Carlos McCord; Javier Navarro-Garcia; et al. (Sustainability Science, 2023)
There is an urgent need for countries to transition their national food and land-use systems toward food and nutritional security, climate stability, and environmental integrity. How can countries satisfy their demands while jointly delivering the required transformative change to achieve global sustainability targets? Here, we present a collaborative approach developed with the FABLE—Food, Agriculture, Biodiversity, Land, and Energy—Consortium to reconcile both global and national elements for developing national food and land-use system pathways. This approach includes three key features: (1) global targets, (2) country-driven multi-objective pathways, and (3) multiple iterations of pathway refinement informed by both national and international impacts. This approach strengthens policy coherence and highlights where greater national and international ambition is needed to achieve global goals (e.g., the SDGs). We discuss how this could be used to support future climate and biodiversity negotiations and what further developments would be needed.

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

In Vitro Assessment of Transporter Mediated Perpetrator DDIs for Several Hepatitis C Virus Direct-Acting Antiviral Drugs and Prediction of DDIs with Statins Using Static Models - Xiaoyan Chu; Grace Hoyee Chan; Robert Houle; Meihong Lin; Jocelyn Yabut; Christine Fandozzi (The AAPS Journal, 2022)

Hereditary cancer panel testing challenges and solutions for the latinx community: costs, access, and variants - Michael P. Douglas; Grace A. Lin; Julia R. Trosman; Kathryn A. Phillips (Journal of Community Genetics, 2022)
Hereditary breast and ovarian cancers (HBOCs) are common among the Latinx population, and risk testing is recommended using multi-gene hereditary cancer panels (HCPs). However, little is known about how payer reimbursement and out-of-pocket expenses impact provider ordering of HCP in the Latinx population. Our objective is to describe key challenges and possible solutions for HCP testing in the Latinx population. As part of a larger study, we conducted semi-structured interviews with key provider informants (genetic counselors, oncologist, nurse practitioner) from safety-net institutions in the San Francisco Bay Area. We used a deductive thematic analysis approach to summarize themes around challenges and possible solutions to facilitating HCP testing in Latinx patients. We found few financial barriers for HCP testing for the Latinx population due to laboratory patient assistance programs that cover testing at low or no cost to patients. However, we found potential challenges related to the sustainability of low-cost testing and out-of-pocket expenses for patients, access to cascade testing for family members, and pathogenic variants specific to Latinx. Providers questioned whether current laboratory payment programs that decrease barriers to testing are sustainable and suggested solutions for accessing cascade testing and ensuring variants specific to the Latinx population were included in testing. The use of laboratories with payment assistance programs reduces barriers to HCP testing among the US population; however, other barriers are present that may impact testing use in the Latinx population and must be addressed to ensure equitable access to HCP testing for this population.

The conduction velocity-potassium relationship in the heart is modulated by sodium and calcium - D. Ryan King; Michael Entz; Grace A. Blair; Ian Crandell; Alexandra L. Hanlon; Joyce Lin; Gregory S. Hoeker; Steven Poelzing (Pflügers Archiv - European Journal of Physiology, 2021)
The relationship between cardiac conduction velocity (CV) and extracellular potassium (K + ) is biphasic, with modest hyperkalemia increasing CV and severe hyperkalemia slowing CV. Recent studies from our group suggest that elevating extracellular sodium (Na + ) and calcium (Ca 2+ ) can enhance CV by an extracellular pathway parallel to gap junctional coupling (GJC) called ephaptic coupling that can occur in the gap junction adjacent perinexus. However, it remains unknown whether these same interventions modulate CV as a function of K + . We hypothesize that Na + , Ca 2+ , and GJC can attenuate conduction slowing consequent to severe hyperkalemia. Elevating Ca 2+ from 1.25 to 2.00 mM significantly narrowed perinexal width measured by transmission electron microscopy. Optically mapped, Langendorff-perfused guinea pig hearts perfused with increasing K + revealed the expected biphasic CV-K + relationship during perfusion with different Na + and Ca 2+ concentrations. Neither elevating Na + nor Ca 2+ alone consistently modulated the positive slope of CV-K + or conduction slowing at 10-mM K + ; however, combined Na + and Ca 2+ elevation significantly mitigated conduction slowing at 10-mM K + . Pharmacologic GJC inhibition with 30-μM carbenoxolone slowed CV without changing the shape of CV-K + curves. A computational model of CV predicted that elevating Na + and narrowing clefts between myocytes, as occur with perinexal narrowing, reduces the positive and negative slopes of the CV-K + relationship but do not support a primary role of GJC or sodium channel conductance. These data demonstrate that combinatorial effects of Na + and Ca 2+ differentially modulate conduction during hyperkalemia, and enhancing determinants of ephaptic coupling may attenuate conduction changes in a variety of physiologic conditions.

Clinacanthus nutans Mitigates Neuronal Death and Reduces Ischemic Brain Injury: Role of NF-κB-driven IL-1β Transcription - Mei-Han Kao; Jui-Sheng Wu; Wai-Mui Cheung; Jin-Jer Chen; Grace Y. Sun; Wei-Yi Ong; Deron R. Herr; Teng-Nan Lin (NeuroMolecular Medicine, 2021)

Noninvasive ultrasound deep brain stimulation of nucleus accumbens induces behavioral avoidance - Lili Niu; Yanchen Guo; Zhengrong Lin; Zhe Shi; Tianyuan Bian; Lin Qi; Long Meng; Anthony A. Grace; Hairong Zheng; Ti-Fei Yuan (Science China Life Sciences, 2020)

A dual luciferase assay for evaluation of skin sensitizing potential of medical devices - Elisabeth Mertl; Elisabeth Riegel; Nicole Glück; Gabriele Ettenberger-Bornberg; Grace Lin; Sabrina Auer; Magdalena Haller; Angelika Wlodarczyk; Christoph Steurer; Christian Kirchnawy; Thomas Czerny (Molecular Biology Reports, 2019)

Effects of Litter Inputs on N2O Emissions from a Tropical Rainforest in Southwest China - Jinbo Gao; Wenjun Zhou; Yuntong Liu; Jing Zhu; Liqing Sha; Qinhai Song; Hongli Ji; Youxing Lin; Xuehai Fei; Xiaolong Bai; Xiang Zhang; Yun Deng; et al. (Ecosystems, 2018)

Clinacanthus nutans Mitigates Neuronal Apoptosis and Ischemic Brain Damage Through Augmenting the C/EBPβ-Driven PPAR-γ Transcription - Jui-Sheng Wu; Mei-Han Kao; Hsin-Da Tsai; Wai-Mui Cheung; Jin-Jer Chen; Wei-Yi Ong; Grace Y. Sun; Teng-Nan Lin (Molecular Neurobiology, 2018)

Mapping QTL for Omega-3 Content in Hybrid Saline Tilapia - Grace Lin; Le Wang; Si Te Ngoh; Lianghui Ji; Laszlo Orbán; Gen Hua Yue (Marine Biotechnology, 2018)

Nutraceuticals in Neurodegeneration and Aging - Wei-Yi Ong; Grace Y. Sun; W. Gibson Wood; Teng-Nan Lin (NeuroMolecular Medicine, 2016)

Clinacanthus nutans Extracts Modulate Epigenetic Link to Cytosolic Phospholipase A2 Expression in SH-SY5Y Cells and Primary Cortical Neurons - Charlene Siew-Hon Tan; Christabel Fung-Yih Ho; Swan-Ser Heng; Jui-Sheng Wu; Benny Kwong-Huat Tan; Yee-Kong Ng; Grace Y. Sun; Teng-Nan Lin; Wei-Yi Ong (NeuroMolecular Medicine, 2016)

Clinacanthus nutans Protects Cortical Neurons Against Hypoxia-Induced Toxicity by Downregulating HDAC1/6 - Hsin-Da Tsai; Jui-Sheng Wu; Mei-Han Kao; Jin-Jer Chen; Grace Y. Sun; Wei-Yi Ong; Teng-Nan Lin (NeuroMolecular Medicine, 2016)

Mapping Quantitative Trait Loci for Omega-3 Fatty Acids in Asian Seabass - Jun Hong Xia; Grace Lin; Xiaoping He; Bu Yunping; Peng Liu; Feng Liu; Fei Sun; Rongjian Tu; Gen Hua Yue (Marine Biotechnology, 2014)

Isolation and characterization of 17 polymorphic microsatellites in the brown mud mussel Glauconome rugosa - Fei Sun; Quanqi Zhang; Juraini Tan; Grace Lin; Gen Hua Yue (Conservation Genetics Resources, 2013)

Microcosm Study of Iron Mobilization and Greenhouse Gas Evolution in Soils of a Plantation-Forested Subtropical Coastal Catchment - Chaofeng Lin; Eloise I. Larsen; Peter R. Grace; James J. Smith (Water, Air, & Soil Pollution, 2012)

Peroxisome Proliferator-Activated Receptor Gamma (PPAR-γ) and Neurodegenerative Disorders - Yu-Chang Chen; Jui-Sheng Wu; Hsin-Da Tsai; Chien-Yu Huang; Jin-Jer Chen; Grace Y. Sun; Teng-Nan Lin (Molecular Neurobiology, 2012)

Aesthetascs in Lysmata spp. shrimp: sexual dimorphism and relationship with social environments - Jing Zhu; Dong Zhang; Junda Lin; Michael S. Grace (Marine Biology, 2012)

Spatial dependence of alveolar angiogenesis in post-pneumonectomy lung growth - Moritz A. Konerding; Barry C. Gibney; Jan P. Houdek; Kenji Chamoto; Maximilian Ackermann; Grace S. Lee; Miao Lin; Akira Tsuda; Steven J. Mentzer (Angiogenesis, 2012)

Novel variant Pro143Ala in HTRA2 contributes to Parkinson’s disease by inducing hyperphosphorylation of HTRA2 protein in mitochondria - Chin-Hsien Lin; Meng-Ling Chen; Grace Shiahuy Chen; Chun-Hwei Tai; Ruey-Meei Wu (Human Genetics, 2011)

Longitudinal associations of blood markers of insulin and glucose metabolism and cancer mortality in the third National Health and Nutrition Examination Survey - Niyati Parekh; Yong Lin; Richard B. Hayes; Jeanine B. Albu; Grace L. Lu-Yao (Cancer Causes & Control, 2010)

Effect of intraluminal pillars on particle motion in bifurcated microchannels - Aslihan Turhan; Akira Tsuda; Moritz A. Konerding; Miao Lin; Lino Miele; Grace Lee; Steven J. Mentzer (In Vitro Cellular & Developmental Biology - Animal, 2008)

Ataxia and pancytopenia caused by a mutation in TINF2 - Elena Tsangaris; Sally-Lin Adams; Grace Yoon; David Chitayat; Peter Lansdorp; Inderjeet Dokal; Yigal Dror (Human Genetics, 2008)

Characterization and cross-species amplification of microsatellites from the endangered Hawksbill turtle (Eretmochelys imbricate) - Grace Lin; Alex Chang; Hon Wah Yap; Gen Hua Yue (Conservation Genetics, 2008)

Implicit solvent simulation models for biomembranes - Grace Brannigan; Lawrence C.-L. Lin; Frank L. H. Brown (European Biophysics Journal, 2006)

Central and peripheral tissue distribution of diclofenac after subcutaneous injection in the rat - R. F. Grace; S. R. Edwards; L. E. Mather; Y. Lin; I. Power (Inflammopharmacology, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Biomimetic Metabolism of Artelinic Acid by Chemical Cytochrome P-450 Model Systems - Olutosin R. Idowu; Ai J. Lin; James M. Grace; James O. Peggins (Pharmaceutical Research, 1997)